Effective presentations : teacher's book - Comfort, Jeremy; York Associates (Oxford : Oxford University Press, 1995)
This book is about: What is the point? Making a Start; Linking the parts; The right kind of language; Visual aids; Body language; Finishing off; Question time; and Putting it all together.
Keywords: English language; Public speaking; Business presentations; Public speaking -- Business English -- Study and teaching -- Foreign speakers -- Audio-visual aids